Tackling Inequality: Asymmetric Vocational Education and Training for Women’s Empowerment - Kusmawaty Matara; Febriyando Febriyando; Sri Yunita Taligansing; Esa Arsyiatul Alfath (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to analyze and reveal the success of the Juriya village program through Asymmetric Vocational Education and Training on community empowerment, especially for women. The study focuses on gender mainstreaming in development through strengthening local planning and budgeting institutions responsive to gender and the environment. This study uses a descriptive qualitative approach, with study subjects including the Juriya vocational village development team, the Wire-G women’s community, the village head, village officials, and the Juriya village women’s community. Data collection used interviews, observation, and documentation. Data analysis techniques were done through data condensation, data display, and conclusion. The results showed that asymmetric vocational education and training significantly impacted women’s empowerment, especially in improving the economic and social status of the women’s community and making them more dexterous and skilled in managing local resources in Juriya village. The conclusion of this study confirms that an education and training approach responsive to gender and the demands of modern industry can effectively empower women at the local level.